Evaluation of growth and survival of juveniles blue swimming crab, Portunus pelagicus (Linnaeus, 1758) in captivity - Kohinoor, S.M. Shoyaib (2019)
Growth and survival of Portunus pelagicus juveniles in captivity were investigated with different bottom substrates, culture environments, feeding and stocking density treatments in captivity. The first experiment was conducted to evaluate the growth and survival of crab juveniles cultured in tanks using three bottom substrates viz. sand, soil and combination of sand and soil. The highest survival of the juveniles at 65.33% was achieved (P < 0.05) using sandy substrates followed by soil (29.33%), sand + soil (28.00%) and control (21.33%). The second experiment was then carried out to evaluate the water quality parameters, growth and body protein composition of P. pelagicus juveniles in recirculating aquaculture system (RAS) in comparison to the conventional culture system (CAS). Results showed that water quality parameters were overall better in RAS with a significantly (P < 0.05) lower level of ammonia-N (0.04 ± 0.10 mg/L) and nitrite-N (0.02 ± 0.07 mg/L) as compared to CAS. The carapace width (46.56 ± 7.05 mm) and protein content (10.26 ± 0.3%) in juvenile crabs were also significantly higher in RAS compared with crab juveniles cultured in CAS (carapace width: 35.95 ± 5.17 mm and protein content: 9.36 ± 0.28%). The third experiment was conducted to determine the effect of different types of the fresh feeds on the growth of P. pelagicus in RAS system. The food source tested were scad fish, squid (Loligo sp.) and Acetes shrimps. The crabs fed with squid showed significantly (P < 0.05) higher carapace width (68.02 ± 3.51 mm) than those fed the scad fish (53.69 ± 3.32 mm) and Acetes shrimps (51.19 ± 3.76 mm). The fourth experiment investigated the growth of P. pelagicus juveniles when fed using commercial shrimp pellet, fresh squid and mixed feed (ratio of shrimp pellet with squid) under three treatments in RAS. The highest carapace width (57.23 ± 3.12 mm) was observed when used mixed feeds for crab juveniles. The different feeding frequencies were then examined to evaluate the growth and survival of juvenile crabs using mixed feeds. The feeding frequency results showed that feeding three times per day exhibited the highest value of carapace width (65.23 ± 1.61 mm) and survival (50.03 ± 0.02%) of P. pelagicus juveniles compared with others. The final experiment was run to see the effect of different stocking densities of P. pelagicus in captivity. The four different stocking densities tested were 16, 20, 24 and 28 individuals / m2. The highest percentage of survival (58.33 ± 0.02%) was observed at 16 individuals / m2 whereas, the lowest was found at 28 individuals / m2 (33.36 ± 2.62%). This research elucidates that the provision of sand substrates can increase the survival of P. pelagicus juvenile in the captive condition. RAS system is highly recommended as it provides optimum water quality parameters with better growth. The practice of mixed feeds, feeding frequency of three times per day and 16 individuals / m2 stocking density is recommended for juvenile culture of blue swimming crab.